Kelayakan rencana bisnis komoditas kesatuan pengelolaan hutan produksi (KPHP) DAS Belayan Provinsi Kalimantan Timur - Rahmadi Rahmadi; Sahrul Uma; Elsy Riawati; Muhammad Ridwansyah (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
KPHP Unit XXVI Belayan Watershed has a management area for production forest and protected forest that has not been optimally utilized. This study aims to develop a business plan strategy in order to optimize the resources of the KPHP Belayan watershed which is oriented towards reducing emissions to achieve sustainable forest management, improving people's welfare, and increasing income. This study use SWOT analysis to determine the right strategy in order to optimize the resources of the KPHP Belayan Watershed. The analysis results show that the commodity business (palm sugar, palm solid sugar, forest honey and kelulut honey, bamboo skewers and carbon trading) by the KPHP Belayan Watershed is financially feasible to be financed. This means that the strategy that must be carried out is to expand the market segmentation of these commodities so that these commodities can advance. Keywords: Belayan watershed, Production forest, Sustainable forest, SWOT